1996
DOI: 10.1139/m96-129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of indoleacetic-acid-producing Bacillus isolates on the nodulation of Phaseolus vulgaris by Rhizobium etli under gnotobiotic conditions

Abstract: Twenty-two Bacillus spp. isolates from the rhizosphere of Phaseolus vulgaris 'Contender' were identified using Biolog™, gas chromatographic fatty acid methyl ester, and 23S rDNA analyses. Some of the Bacillus isolates produced significant amounts of the phytohormone indoleacetic acid (IAA) when grown in a liquid culture medium supplemented with 100 μg L-tryptophan/L; less IAA was produced in culture medium not supplemented with L-tryptophan. Thin-layer chromatography, high-performance liquid chromatography, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 47 publications
3
40
0
6
Order By: Relevance
“…melhorou a nodulação e fixação de N 2 , biomassa vegetal e produção de grãos em várias espécies de leguminosas, como alfafa (Bolton et al, 1990), soja (Dashti et al, 1998), feijão-mungo-verde (Sindhu et al, 1999) e grão-de-bico (Goel et al, 2002 Bradyrhizobium spp. pode melhorar a nodulação e crescimento de plantas de feijão e soja, respectivamente (Srinivasan et al, 1997;Camacho et al, 2001;Bai et al, 2003). Os mecanismos utilizados pelas rizobactérias para promover nodulação e fixação de N 2 são, na sua maioria, desconhecidos ou permanecem ambíguos.…”
Section: Introductionunclassified
“…melhorou a nodulação e fixação de N 2 , biomassa vegetal e produção de grãos em várias espécies de leguminosas, como alfafa (Bolton et al, 1990), soja (Dashti et al, 1998), feijão-mungo-verde (Sindhu et al, 1999) e grão-de-bico (Goel et al, 2002 Bradyrhizobium spp. pode melhorar a nodulação e crescimento de plantas de feijão e soja, respectivamente (Srinivasan et al, 1997;Camacho et al, 2001;Bai et al, 2003). Os mecanismos utilizados pelas rizobactérias para promover nodulação e fixação de N 2 são, na sua maioria, desconhecidos ou permanecem ambíguos.…”
Section: Introductionunclassified
“…Tem sido demonstrado que as taxas de hormônios nas plantas podem ser alteradas pelos flavonóides liberados, ocasionando um desbalanço hormonal endógeno na raiz (Hirsch, 1992). Essas alterações levariam a divisões celulares na raiz, produzindo sítios de infecção adicionais para o rizóbio e, conseqüentemente, aumento na nodulação (Srinivasan et al, 1996(Srinivasan et al, , 1997. A organogênese do nódulo claramente envolve os fitormônios (Hirsch & Fang, 1994), mas ainda não está claro se os níveis de fitormônios elevados nos nódulos são resultado da resposta da planta à infecção da bactéria ou de uma função direta da atividade da bactéria.…”
Section: Figura 4 Atividade Da Enzima ß-Glucuronidase Resultante Daunclassified
“…Resultados recentes apresentados por Srinivasan et al (1996Srinivasan et al ( , 1997 De maneira geral, houve uma tendência de inibição da nodulação pelo suprimento de N mineral. Embora a inibição da nodulação por N combinado seja conhecida há bastante tempo, os mecanismos pelos quais ela ocorre ainda são muito pouco conhecidos (Streeter, 1988;Heidstra et al, 1997).…”
Section: Figura 4 Atividade Da Enzima ß-Glucuronidase Resultante Daunclassified
“…It was shown that coinoculation of Rhizobium etli TAL 182 with Bacillus sp. induced root hair proliferation in Phaseolus vulgaris and enhanced nodulation of P. vulgaris by Rhizobium (Srinivasan et al 1996). Coinoculation with both bacterial species also facilitated heterologous nodulation of Rhizobium Tal 182 on Phaseolus acutifolius (Srinivasan et al 1996).…”
Section: Rhizobium and Nodulation Promoting Rhizobacteriamentioning
confidence: 94%
“…induced root hair proliferation in Phaseolus vulgaris and enhanced nodulation of P. vulgaris by Rhizobium (Srinivasan et al 1996). Coinoculation with both bacterial species also facilitated heterologous nodulation of Rhizobium Tal 182 on Phaseolus acutifolius (Srinivasan et al 1996). Rhizobium etli is a narrow host range microsymbiont specific for nodulation on P. vulgaris whereas P. acutifolius belongs to the cowpea cross inoculation group and has a very specialized bradyrhizobial requirement for nodulation (Somasegaran et al 1991).…”
Section: Rhizobium and Nodulation Promoting Rhizobacteriamentioning
confidence: 99%